Antecedents and Consequences of Attitudes toward Donation-Based Crowd-Funding Platforms - Namhyun Um (Journal of Theoretical and Applied Electronic Commerce Research)
The landscape of fundraising has undergone a transformative shift with the rise in donation-based crowdfunding platforms. This study investigates the multifaceted factors shaping individuals’ attitudes toward these platforms, with a focus on key antecedents. Examining their impact on donation intentions and electronic word-of-mouth intentions, this research draws from a sample of 326 college students. Our results affirm the critical roles of perceived usefulness, ease of use, credibility, and self-efficacy in influencing attitudes. Additionally, attitudes significantly contribute to both donation and electronic word-of-mouth intentions. Structural model modifications underscore the interdependence of these factors, enhancing the model fit. Our findings offer practical insights for platform administrators, campaign creators, and stakeholders engaged in online philanthropy, highlighting the importance of user-friendly designs, trust-building, and user confidence for successful crowdfunding campaigns.